TINJAUAN KRITIS TERHADAP PEMBOROSAN PANGAN: BESARAN, PENYEBAB, DAMPAK, DAN STRATEGI KEBIJAKAN - Mewa Ariani; Herlina Tarigan; Achmad Suryana (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2021)
Food loss and waste are one of the indicators of Sustainable Development Goals (SDGs), namely goal 12: ensure sustainable food consumption and production patterns. Indonesia is committed to achieving the targets set out in the SDGs, one of which is target 12.3: to reduce food loss and waste by half by 2030. Achieving this target is beneficial for achieving national food and nutrition security, and environmental sustainability. This paper is a scientific review aimed at analyzing the magnitude, causes, impacts, and policy strategies for reducing food waste. The results of the analysis show that the percentage of food waste in the last two decades tends to increase. The largest proportion of food waste occurs at the household level. The main cause is the behavior of household food consumption patterns, ranging from planning, purchasing, and processing up to consumption, which do not aware that food waste has impacted not only individuals but also society in the form of economic, social, and environmental losses. Therefore, efforts to reduce food waste need to be carried out comprehensively and sustainably, considering that changing people's food consumption behavior takes a relatively long time. Another effort that needs to be done is to change the mindset of each individual toward the value of food through formal education from an early age and non-formal socialization by utilizing various communication media.